PENGARUH PENAMBAHAN TEPUNG JAHE EMPRIT(Zingiber officinale var. Amarum) PADA PAKAN TERHADAP PERTUMBUHAN DAN DAYA HIDUP IKAN NILA (Oreochromis niloticus) - Ahmad Hadi Ripaki; Farikhah Farikhah; Andi Rahmad Rahim (Universitas Muhammadiyah Gresik, 2018)
Tilapia (Oreochromis niloticus) is a type of fish that has high economic value.Cultivation is determined by two factors: fish disease and growth. Among the results ofimmunostimulant studies added in the diet can increase the nonspecific immune response as wellas increase the growth of fish, immunostimulant ingredients are one of ginger emprit (Zingiberofficinale var Amarum). This study aims to analyze the effect of the addition of ginger flouremprit to growth rate, survival rate and feed conversion ratio of tilapia fish. The research methodused was Completely Randomized Design (CRD) consisting of 4 with 3 replications, namely:treatment A = 5, B = 7.5, C = 10 g/kg of feed and control (no addition of ginger). The mainparameters observed were specific growth rate, absolute weight, survival rate and feedconversion ratio. The supporting parameters are water quality consisting of temperature, pH andDO. Analysis of the data using ANOVA if influenced by further Tukey test (p <0,05). Theresults showed that the best growth in this study was in treatment with a dose of 7.5 g/kg of feedwith an absolute weight of 5.40 ± 0.34 g, a specific growth rate of 2.41 ± 0.08%/day, survivalrate that is equal to 90 ± 0,0%, and feed conversion ratio of 3.6 ± 0.15 g.